1988
DOI: 10.1002/jnr.490190412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin and‐like growth factor (IGF‐I)on oligodendrocyte‐enriched glial culture

Abstract: The brains from 1-week-old rat pups were used to prepare cultures of glial cells. After 24 hr in culture the cells were changed to a chemically defined serum-free medium (CDM). We have used antibodies against gangliosides (monoclonals A2B5 and LB1) and against galactocerebrosides to monitor the influence of insulin on the development of oligodendrocytes from precursor cells. In these oligodendrocyte-enriched cultures we investigated the influence of insulin and IGF-I on the activity of the marker enzymes 2',3'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…This time is equivalent to 14 days postnatal, and our results for CST maximal activity (12 DIV) are thus in accordance with these previous observations. Our results are also in accordance with those of van der Pal et al (1988) who observed a maximal 35S incorporation into sulfatides at a time equivalent to 12 days postnatal in OL enriched glial cultures.…”
Section: Basal Cst Activitysupporting
confidence: 95%
“…This time is equivalent to 14 days postnatal, and our results for CST maximal activity (12 DIV) are thus in accordance with these previous observations. Our results are also in accordance with those of van der Pal et al (1988) who observed a maximal 35S incorporation into sulfatides at a time equivalent to 12 days postnatal in OL enriched glial cultures.…”
Section: Basal Cst Activitysupporting
confidence: 95%
“…The fact that the time course of IGF-I receptor immunostaining in oligodendroglia parallels the return of myelinrelated proteins as shown by levels of transcripts in the present study, by the presence of myelin proteins in oligodendroglia (33), and by myelin regeneration in electron micrographs (21,22,34) suggests that IGF action in this setting may stimulate functions of differentiated oligodendroglia, as demonstrated in vitro (7)(8)(9)(10)20). Thus, we conclude from the present findings that oligodendroglial injury and/or myelin breakdown trigger astroglial IGF-I production and that IGF-I released from astrocytes may diffuse in a paracrine mode to act on IGF-I receptors on nearby oligodendroglia and stimulate oligodendroglial functions that produce myelin regeneration.…”
Section: Discussionsupporting
confidence: 72%
“…It promotes the mitosis of sympathetic neuroblasts, the survival of fetal neurons, and the stimulation of neurite outgrowth in motor and sensory neurons, and it induces oligodendrocyte differentiation and myelin synthesis (3)(4)(5)(6)(7)(8)(9)(10). These effects are mediated by the type I IGF receptor, which is a membranebound tyrosine kinase with significant homology to the insulin receptor (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, insulin is known to modify the metabolic activities of astroglial cells through the stimulation of glucose uptake and protein and lipid synthesis (Kum et al, 1987(Kum et al, , 1988Van der Pal et al, 1988). Because TOF-I does not produce OPT hydrolysis in astrocytes, other mechanisms of action may be related to the effects of this polypeptide, i.e., mitogenesis of astrocytes and promotion of glial cell development (Ballotti et al, 1987;Van der Pal et al, 1988). It is interesting that TGF-I receptors, IRS-1, and P1-3' kinase have been identified in rat brain and are components of another signal transduction pathway involved in the mechanism of both TGF-I and insulin action (Folli et al, 1994).…”
Section: Fig 7 A-d: Effect Of Ige-l or Igf-li On [mentioning
confidence: 99%